2017
DOI: 10.1103/physrevlett.119.043903
|View full text |Cite
|
Sign up to set email alerts
|

Breaking the Temporal Resolution Limit by Superoscillating Optical Beats

Abstract: Band-limited functions can oscillate locally at an arbitrarily fast rate through an interference phenomenon known as superoscillations. Using an optical pulse with a superoscillatory envelope we experimentally break the temporal Fourier-transform focusing limit with a temporal feature that is approximately three times shorter than the duration of a transform-limited Gaussian pulse having a comparable bandwidth while maintaining 30% visibility. We experimentally demonstrate the ability of such signals to achiev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 31 publications
0
37
0
Order By: Relevance
“…The phenomenon was first experimentally observed in the diffraction of coherent light by a quasicrystal array of nanoholes in a metal screen and its potential for spatial and temporal super-resolution focusing and imaging without evanescent fields was recognized, see Refs. [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The phenomenon was first experimentally observed in the diffraction of coherent light by a quasicrystal array of nanoholes in a metal screen and its potential for spatial and temporal super-resolution focusing and imaging without evanescent fields was recognized, see Refs. [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Superoscillations have relevance in all areas of physics where waves are superposed, e.g., in quantum mechanics [20]. It has also been proposed and demonstrated that superoscillations could be exploited to obtain improved optical resolution [21][22][23][24], ultrasonic lateral resolution [25], or radiofrequency measurement in bandwidth-limited systems [26]. The main problem with the practical application of superoscillations in many areas has been their small amplitude.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the super‐oscillation interference, super‐oscillation lens (SOL) provides an unprecedented avenue for far‐field noninvasive super‐resolution imaging, as demonstrated in experiments . SOL has been successfully applied to the subdiffraction focusing and imaging as well as the heat assisted magnetic recording in confocal scanning system . The key point of super‐oscillation imaging is appropriate pupil filter in imaging optics, which is usually realized by binary amplitude elements, spatial light modulators or specially designed nanostructures .…”
Section: Introductionmentioning
confidence: 99%